First-Year Outcomes of Critical Congenital Heart Disease Screening in Maryland. (August 2019) - Badawi, Deborah; Watson, Johnna; Maschke, Steven; Reid, Lawrence
Objectives . Newborn screening for critical congenital heart disease (CCHD) was added to the Recommended Uniform Screening Panel in 2011, and states have been gradually adding pulse oximetry as point-of-care screening to panels. Few data are available on the effectiveness of pulse oximetry as a mandated screening. This study describes outcomes of the first year of screening in Maryland. Methods . A web-based data collection tool for screening results and outcomes, eScreener Plus, was utilized. Data collected from the start of screening from September 1, 2012, to December 31, 2013, were analyzed. Well-baby nursery data were evaluated separately from neonatal intensive care unit (NICU) data to determine whether setting influenced effectiveness. Results . In the first 15 months of newborn screening for CCHD in Maryland, 4 asymptomatic infants were diagnosed with a critical cardiac condition by newborn screening. Eleven infants passed but were later identified with a primary or secondary target condition. Seventy-one percent of infants with CCHD were identified prenatally or by clinical signs and symptoms. Pulse oximetry screening for CCHD had a specificity of more than 99% in both the well-baby nursery and the NICU. Sensitivity in the well-baby nursery was 10% and 60% in the NICU. Conclusion . Further investigation and interpretation of specific protocols that were used and outcomes of screening is needed for continued refinement of the well-baby algorithm and NICU protocol development. Pulse oximetry screening in newborns provides valuable clinical information, but many infants with CCHD are still not identified with current protocols.